Bandgap tuning of pseudoboehmite nanoparticles induced by quantum confinement. Issue 15 (1st August 2022) - Yang, Wenli; Cortés Vega, Fernando D.; Ahmadi, Kamyar; Rani, Arti; Hadjiev, Viktor G.; Calderon, Hector A.; Brankovic, Stanko R.; Robles Hernández, Francisco C.
Abstract: In this work we report the bandgap tuning of pseudoboehmite achieved by high energy ball milling. The milling process of pseudoboehmite was performed using a SPEX 8000 mill for of up to 10 h. Pseudooehmite powders were characterized before and after milling by X-ray diffraction, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy (XPS) and electron energy loss spectroscopy (EELS). XRD results confirmed that the pseudoboehmite structure is preserved for 10 h of milling. The crystallite size of pseudoboehmite was estimated by Scherer equation, observing a constant increase with milling time from 2.72 nm to 3.18 nm. The pseudobohemite has a reduction in d-spacing with milling in the " c-axis ", but an enlargement in the " a-b directions ". The " c-axis " modification is due to water release, while the " a-b-plane " enlargement is attributed to cold welding during milling. The XPS and EELS analyses demonstrated a bandgap tuning effect from 7.11 eV to 6.20 eV in the raw and milled pseudoboehmite for 10 h. The results were demonstrated analytically.